Analisis Peran Orangtua dalam Menumbuhkan Kedisiplinan Anak Usia 5-6 Tahun di TK Al Ihsan - Bangun , Suci Yamasintha; Kamtini, Kamtini (Universitas Negeri Medan, 2025)
This study aims to determine the role of parents in fostering discipline in early childhood in Al-Ihsan Kindergarten Medan, especially when queuing. This study is a type of descriptive qualitative research using data analysis techniques from data collection, reduction, presentation, and conclusion. The subjects in this study were 6 children in class B in the age range of 5-6 years at Al Ihsan Kindergarten. The object of this study is how the role of parents in fostering discipline in early childhood, the data of which was collected through observation and interviews with parents. The findings of the researcher showed that 4 out of 6 children in the queuing process had not developed optimally. This happens because parents have not fully given an important role in the process of fostering children's discipline, especially when queuing.